Q. 54.6( 8 Votes )

# For what value of a, the divisions of two polynomials (ax^{3} + 3x^{2} – 3) and (2x^{3} – 5x + a) by (x – 4) give the same remainder —let us calculate and write it.

Answer :

Let the two polynomials be,

P(x) = ax^{3} + 3x^{2} – 3 …(i)

Q(x) = 2x^{3} – 5x + a …(ii)

Now, we understand by the question that,

P(x) and Q(x) divided by (x – 4) gives the same remainder.

We need to find zero of the linear polynomial, (x – 4).

To find zero, put (x – 4) = 0

⇒ x – 4 = 0

⇒ x = 4

By Remainder theorem that says, f(x) is a polynomial of degree n (n ≥ 1) and ‘a’ is any real number. If f(x) is divided by (x – a), then the remainder will be f(a).

Here, a = 4.

This means, remainder when P(x) is divided by (x – 4) is P(4).

⇒ Remainder = P(4)

⇒ Remainder = a(4)^{3} + 3(4)^{2} – 3

⇒ Remainder = 64a + 48 – 3

⇒ Remainder = 64a + 45 …(iii)

And remainder when Q(x) is divided by (x – 4) is Q(4).

⇒ Remainder = Q(4)

⇒ Remainder = 2(4)^{3} – 5(4) + a

⇒ Remainder = 128 – 20 + a

⇒ Remainder = 108 + a …(iv)

When P(x) and Q(x) are divided (x – 4) , they leave same remainder.

Comparing equations (iii) and (iv), we have

64a + 45 = 108 + a

⇒ 64a – a = 108 – 45

⇒ 63a = 63

⇒

⇒ a = 1

Thus, a = 1.

Rate this question :

By applying Remainder Theorem, let us calculate and write the remainder that I shall get in every cases, when x^{3} – 3x^{2} + 2x + 5 is divided by

x – 2

West Bengal MathematicsBy applying Remainder Theorem, let us calculate and write the remainder that I shall get in every cases, when x^{3} – 3x^{2} + 2x + 5 is divided by

2x + 1

West Bengal MathematicsBy applying Remainder Theorem, let us calculate and write the remainders, that I shall get when the following polynomials are divided by (x – 1).

11x^{3} – 12x^{2} – x + 7

By applying Remainder Theorem, let us calculate and write the remainders, that I shall get when the following polynomials are divided by (x – 1).

4x^{3} + 4x^{2} – x – 1

Applying Remainder Theorem, let us calculate whether the polynomial.

P(x) = 4x^{3} + 4x^{2} – x – 1 is a multiple of (2x + 1) or not.

Applying Remainder Theorem, let us write the remainders, when,

the polynomial x^{3} – ax^{2} + 2x – a is divided by (x – a)

By applying Remainder Theorem, let us calculate and write the remainders, that I shall get when the following polynomials are divided by (x – 1).

x^{3} – 6x^{2} + 13x + 60

Let us show that if n be any positive integer (even or odd), the x – y never be a factor of the polynomial x^{n} + y^{n}.